Effect of nanocavities on Ge nanoclustering and out-diffusion in SiO2. (14th December 2016) - Li, Chen; Feng, Honglei; Liu, Bin; Liang, Wenshuang; Liu, Guiju; Ross, Guy G; Wang, Yiqian; Barba, David
Abstract: Germanium nanocrystals (Ge-ncs) were synthesized by implantation of Ge + ions into the fused silica, followed by a thermal annealing at 1000 °C. High-resolution transmission electron microscopy was employed to characterize both the morphology of the formed Ge-ncs and the evolution of their depth-distribution as a function of annealing durations. The formation of nanocavities in the vicinity of nanocrystal/SiO2 interface is evidenced, as well as their influence on the release of the compressive stress exerted on Ge-ncs by surrounding SiO2 . Some Ge-ncs are found inside nanocavities, and can move into the implanted layer through a nanocavity-assisted diffusion mechanism. This finding sheds light on a new process that can explain the non-uniformity of the Ge-nanocrystal spatial distribution.